"Palinología de la Formación Bajo de Véliz (Pérmico Inferior), San Luis, Argentina: revisión sistemática y consideraciones bioestratigráficas" (Ameghiniana, 2014)
"The original palynological samples studied by Menéndezfram the Bajo de Véliz Formation (San Luis, Argentina), were revised. This stratigraphic unit has yieldedone of the few Permian palynological associations recorded fram the Paganzo Basin. Some species, suchas: Latusipollenites? ouadrisaccatus Marques- Toigo, Hamiapollenites [usiformis Marques- Toigo,Protonaploxvpinus limpidus (Balme and Hennelly) Hart, Marsupipollenites striatus (Balme and Hennelly)Foster, and Vittatina subsaccaia Samoilovich, were identified in the assemblage for the first time. The occurrenceof Barakarites rotaius (Balme and Hennelly) Bharadwaj and Tiwari, Apiculatisporis cornuius (Balmeand Hennelly) Heeg and Bose, Fusacolpites [usus Bose and Kar, Protohaploxypinus amplus (Balme andHennelly) Hart, Verrucosisporites patelliformis (Menéndez) nov. comb., and Granulatisporites sp. d. G. trisinusBalme and Hennelly, is confirmed. The presence of these species supports the inclusion of this palynologicalassociation in the Early Permian Argentinian Fusacolpiies [usus- Vittatina subsaccata Biozone."